PERBEDAAN LAJU ENDAP DARAH SEBELUM DAN SESUDAH PEMBERIAN AIR KELAPA HIJAU (Cocos nucifera L) PADA PEKERJA BAGIAN PENGECATAN DI INDUSTRI KAROSERI SEMARANG - Rachmawati, Rizka Laila; Setiani, Onny; Darundiati, Yusniar Hanani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Workers in the painting department of carrosserie industry was one of the workers with high risk exposure of lead in the workplace. Pb can affect heme synthesis that would cause damage of the blood. The damage of blood causes the abnormal number and size of red blood cells that can impact on the high Erythrocyte Sedimentation Rate (ESR). Green coconut water was known for its content of tanin or antidote agent that can break down toxic substances in the body. The purpose of this study was to determine differences of erythrocyte sedimentation rate before and after consuming green coconut water on the painting department workers in carrosserie industry, Semarang. This research was a quasi-experimental research with one group pre-test post-test design. Population in this study was 53 workers in the painting department and sample used was 32 people by using purposive sampling technique. Analysis of the data use Wilcoxon test with  significance level 5%. Results of statistical analysis obtained p value=0.08 for ESR 1 hour and 0.220 for ESR 2 hours. From the result of this study concluded that there was no difference in the ESR before and after consuming green coconut water but the average ESR of workers were above normal values (10 mm / hour). It was advisable to do further tests on workers who had high ESR values and workers should always use standard masks to reduce lead exposure in the workplace.